Pengaruh Pola Asuh Orang Tua Terhadap Kecerdasan Emosional Anak Usia Dini, di Tk Negeri Pembina Kec. Kota Timur - Magfira Biludi; Masita Siyuta; Wulandari Dasi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The development of emotional intelligence is greatly influenced by parenting patterns. Therefore, children's emotional intelligence needs to be formed during the pre-school period where there is reinforcement from the environment and parenting patterns obtained from teachers. This study aims to strengthen emotional intelligence that influences early childhood parenting patterns, informing children to control their emotions, overcome fear, dare and be ready to socialize without shame with their peers. This method is a descriptive qualitative study. The sample population of pre-school children at Pembina State Kindergarten, East City District. The total used in this study was group B2 at Pembina State Kindergarten, totaling 16 people consisting of 7 girls and 10 boys. This study used an observation method obtained from children's activities observed during the process of activities in the classroom about emotions.